Formative Usability Evaluation of vINCI Application - Dragoș-Daniel IORDACHE1; Irina CRISTESCU1; Ion Alexandru MARINESCU1; Lidia BAJENARU1; 2 (Communications of International Proceedings, 2021)
Recently, there has been a considerable growth of the applications for older people as embedded information technologies have expanded into almost all sectors of the economy: government, industry, commerce, education and health. These scientific and technical advances have made usability evaluation of software systems particularly important for the development of stable and quality applications. The aim of this study is to present the results of a formative usability evaluation of a mobile application (the vINCI app) that allows the user to monitor his/her wellbeing and quality of life. In order to carry out this task, the heuristic evaluation method was chosen in order to identify and document the usability problems. The method considers a small set of evaluators that examine the application interface and evaluate it using recognized principles of usability, known as heuristics. The evaluation based on the set of specific tasks led to results that highlighted a series of usability problems that will be presented to developers with the recommendation to be remedied in the next development iterations.
Keywords: Usability Evaluation; vINCI Application; Formative Evaluation; Heuristic Evaluation.